The impact of digital transformation for sustainable business: the meditating role of corporate governance and financial performance - Indra Siswanti; Hosam Alden Riyadh; Lenny C. Nawangsari; Yusliza Mohd Yusoff; Mas Wahyu Wibowo (Cogent Business & Management, 2024)
This paper aims to develop a model of sustainable business for Islamic rural banks in Indonesia through the transformation of digital, corporate governance, and financial performance. To achieve this objective, the quantitative research method was used, and the population in this research is 165 Islamic rural banks in Indonesia, while the sample used in this research is 30 Islamic rural banks in the West Java region from 2016 to 2021. The data used in this study is secondary data derived from financial statements and annual reports and analyzed using Partial Least Square (PLS). The research findings highlighted first that digital transformation significantly influences sustainable business. Second, digital transformation significantly influences corporate governance, and third, digital transformation significantly influences financial performance. Fourth, corporate governance has an insignificant influence on sustainable business for Islamic rural banks in Indonesia. Fifth, financial performance significantly influences sustainable business for Islamic rural banks in Indonesia. Sixth, corporate governance does not mediate the effect of digital transformation on sustainable business for Islamic rural banks in Indonesia. Seventh, financial performance is able to mediate the effect of digital transformation on sustainable business for Islamic rural banks in Indonesia. The practical contribution of this study offers empirical evidence for Islamic rural institutions regarding the impact of digital transformation on the sustainability of Islamic rural banks in the context of the dynamic digital economy and technological industry. While the topic of banks' digital transformation has garnered significant attention, the focus has primarily been on a macro level. The findings of this study show top management that digital transformation can potentially serve as a form of market value management. Additionally, this research might serve as a valuable resource for digital transformation organizations seeking to enhance their sustainability initiatives and expedite their progress in the realm of sustainable business practices, particularly for Islamic rural banks in Indonesia. Furthermore, the present study has demonstrated the importance and potential for digital transformation within the Islamic banking sector, hence offering a promising avenue for Islamic rural banks to enhance their operational efficiency and client satisfaction. Considering that limited attention has been given to studies of the relationship between digital transformation and sustainable business in Indonesian Islamic rural banks, this study contributes to the existing literature by examining digital transformation as a new view in explaining and understanding Indonesian Islamic rural banks, which fills the gap because prior research on the topic of digital transformation in Indonesia's Islamic banking sector has mostly ignored management viewpoints on internal corporate governance processes.This research has developed a model of sustainable business for Islamic rural banks in Indonesia through the transformation of digital, corporate governance, and financial performance. The research used a quantitative research method and focused on a population of 165 Islamic rural banks in Indonesia. The sample for this study consisted of 30 Islamic rural banks in the West Java region from 2016 to 2021. The research findings highlighted first that digital transformation significantly influences sustainable business. Second, digital transformation significantly influences corporate governance, and third, digital transformation significantly influences financial performance. Fourth, corporate governance has an insignificant influence on sustainable business. Fifth, financial performance significantly influences sustainable business. Sixth, corporate governance does not mediate the effect of digital transformation on sustainable business. Seventh, financial performance is able to mediate the effect of digital transformation on sustainable business for Islamic rural banks in Indonesia.
Keywords: 650; Sustainable business; digital transformation; corporate governance; financial performance